The Limited Capacity of Sleep-Dependent Memory Consolidation - Feld, Gordon B.; Weis, Patrick P.; Born, Jan (Frontiers in Psychology, 2016)
Sleep supports memory consolidation. However, the conceptually important influence of the amount of items encoded in a memory test on this effect has not been investigated. In two experiments, participants (n=101) learned lists of word-pairs varying in length (40, 160, 320 word-pairs) in the evening before a night of sleep (sleep group) or of sleep deprivation (wake group). After 36 h (including a night allowing recovery sleep) retrieval was tested. Compared with wakefulness, post-learning sleep enhanced retention for the 160 word-pair condition (p < 0.01), importantly, this effect completely vanished for the 320 word-pair condition. This result indicates a limited capacity for sleep-dependent memory consolidation, which is consistent with an active system consolidation view on sleep’s role for memory, if it is complemented by processes of active forgetting and/or gist abstraction. Whereas the absolute benefit from sleep should have increased with increasing amounts of successfully encoded items, if sleep only passively protected memory from interference. Moreover, the finding that retention performance was significantly diminished for the 320 word-pair condition compared to the 160 word-pair condition in the sleep group, makes it tempting to speculate that with increasing loads of information encoded during wakefulness, sleep might favour processes of forgetting over consolidation.